2017
DOI: 10.18178/ijfe.3.1.23-28
|View full text |Cite
|
Sign up to set email alerts
|

Textural Properties of Herby Cheese

Abstract: Herby (Otlu) cheese is a traditional cheese variety which is manufactured broadly in the eastern and southeastern regions of Turkey. In this study the textural properties of herby cheese containing various herbs sold in the markets was determined. The textural characteristics of traditional cheeses were different from industrial herby cheeses, particularly depending on manufacturing practices as well as raw milk composition, herbs, salt, etc. Traditional herby cheese had lower sensory scores for color, fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…In recent years, studies on Herby cheese consisted mainly of the production technique of Herby cheese (Coşkun, 1995; 2005; Emirmustafaoğlu & Coşkun, 2012; Hayaloğlu & Fox, 2008; Tarakci & Temiz, 2009), the effect of different herbs on the composition of Herby cheese (Andic, Tuncturk, Javidipour, & Genccelep, 2015; Coşkun & Tunçtürk, 2000; Kavaz, Bakırcı, & Kaban, 2013; Tarakci, Durmaz, & Sagun, 2005; Tarakci & Kucukoner, 2006; Tarakci, Temiz, Aykut, & Turhan, 2011), comparison of Herby cheese produced by traditional and industrial methods (Kose & Ocak, 2019; Ocak, Javidipour, & Tuncturk, 2014; Tuncturk, Ocak, & Kose, 2014), and researches of Herby cheese samples obtained from the market (Andic et al., 2010; Ekici, Okut, İşleyici, Sancak, & Tuncay, 2019; Eralp, 1953; Hayaloglu & Karabulut, 2013; Isleyici, 1999; İsleyici & Akyuz, 2009; Koyuncu & Tuncturk, 2020; Kurt, 1968; Kurt & Akyüz, 1984; Ocak & Köse, 2010; 2018; Ozcan, Yılmaz‐Ersan, Akpinar‐Bayizit, & Delikanli‐Kiyak, 2017; Ozrenk, Kose, & Ekin, 2009; Sancak, 1989; Sancak, Boynukara, & Yardımcı, 1993; Sönmezsoy, 1994; Tuncay & Sancak, 2018). Researches on Herby cheese samples obtained from the market were also evaluated with some routine and physical, chemical properties, and microbiological aspects of Herby cheese samples.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies on Herby cheese consisted mainly of the production technique of Herby cheese (Coşkun, 1995; 2005; Emirmustafaoğlu & Coşkun, 2012; Hayaloğlu & Fox, 2008; Tarakci & Temiz, 2009), the effect of different herbs on the composition of Herby cheese (Andic, Tuncturk, Javidipour, & Genccelep, 2015; Coşkun & Tunçtürk, 2000; Kavaz, Bakırcı, & Kaban, 2013; Tarakci, Durmaz, & Sagun, 2005; Tarakci & Kucukoner, 2006; Tarakci, Temiz, Aykut, & Turhan, 2011), comparison of Herby cheese produced by traditional and industrial methods (Kose & Ocak, 2019; Ocak, Javidipour, & Tuncturk, 2014; Tuncturk, Ocak, & Kose, 2014), and researches of Herby cheese samples obtained from the market (Andic et al., 2010; Ekici, Okut, İşleyici, Sancak, & Tuncay, 2019; Eralp, 1953; Hayaloglu & Karabulut, 2013; Isleyici, 1999; İsleyici & Akyuz, 2009; Koyuncu & Tuncturk, 2020; Kurt, 1968; Kurt & Akyüz, 1984; Ocak & Köse, 2010; 2018; Ozcan, Yılmaz‐Ersan, Akpinar‐Bayizit, & Delikanli‐Kiyak, 2017; Ozrenk, Kose, & Ekin, 2009; Sancak, 1989; Sancak, Boynukara, & Yardımcı, 1993; Sönmezsoy, 1994; Tuncay & Sancak, 2018). Researches on Herby cheese samples obtained from the market were also evaluated with some routine and physical, chemical properties, and microbiological aspects of Herby cheese samples.…”
Section: Introductionmentioning
confidence: 99%
“…Sweetness represented a positive correlation with butane‐2,3‐dione ( r = 0.888, p < 0.05). Cheesy odor is another sensory property previously reported for traditional cheeses (Ercan et al., 2011; Ozcan et al., 2017) and pointed more correlations with free fatty acids. While our data for Kope cheese revealed a positive correlation between this odor with esters and ketones such as ethyl octanoate ( r = 0.993, p < 0.05), 2‐heptanone ( r = 0.900, p < 0.05), and 2‐nonanone ( r = 0.932, p < 0.05).…”
Section: Sensory Evaluationmentioning
confidence: 62%
“…The increase in moisture content decreases hardness, while an increase in fat content increases springiness. Ozcan et al (2017) reported that raw milk composition, raw milk processes, heat treatment process, pH, type of the plant, salt, starter culture type effected the textural properties of herby cheese. In the present study, the textural properties of hardness, adhesiveness, springiness, gumminess, and chewiness parameters were analyzed on the 1 st and 30 th day of storage ( Table 5).…”
Section: Textural Properties Of Mozzarella Cheesementioning
confidence: 99%
“…Mozzarella cheese is a nutrient characterised by its fresh taste, softness, slightly sour and creeping when heated taste and is preferred due to these properties (Illupapalayam et al, 2013). Ozcan et al (2017) reported that the plant species and production methods affected the sensory properties of herby cheese products and traditional methods provide better taste for the consumers. In the present study, Mozzarella cheese samples were analysed for colour, flavour, texture and overall acceptance properties.…”
Section: Sensory Properties Of Mozzarella Cheesementioning
confidence: 99%